A 3-Port Network-Based Capacitance Measurement Method for Asymmetric Half-Bridge Power Modules - Jaewon Rhee; Seongho Woo; Yujun Shin; Jiseong Kim; Seungyoung Ahn (IEEE Access, 2025)
This paper proposes a method to measure the capacitance of an asymmetric half-bridge power module using a single 3-port S-parameter measurement. The capacitance of a power module originates from power semiconductors including the package and affects switching timing and loop impedance changes during operation, making it essential to determine these values before design. Conventionally, capacitance between terminals is measured using the principle of LCR meters, which extract capacitance by measuring the ratio of voltage to current. However, asymmetric power modules, such as those designed for synchronous buck converters with asymmetric high-side and low-side semiconductors, require a new approach. Asymmetric half-bridge modules with new packaging structures have six different capacitances, which complicates measurement. Therefore, this study proposes a method to measure the capacitance of asymmetric power modules using a single measurement based on a 3-port network theory. This approach simplifies the process by leveraging a commonly used network analyzer, achieving capacitance extraction with a single measurement. The proposed method was compared with vendor-provided capacitance values, showing a maximum difference of approximately 10.9%.